Features to consider in land cover classification based on random forest (Mongolian Journal of Geography and Geoecology, 2024)
In some modern digital image processing systems, different machine learning and high-level processing algorithms are being developed. A researcher can obtain high-quality thematic results by correctly and optimally determining the parameter values in the algorithm based on his or her own knowledge. This research aims to perform a land cover classification using a machine learning random forest (RF) classification algorithm on the SNAP Toolbox system and demonstrate how to adjust the classification parameters for efficient decision-making. In order to increase the classification accuracy, the study uses 3 different combinations of the integrated optical and synthetic aperture radar (SAR) data sets. The area in the southern part of Ulaanbaatar, the capital city, was selected as a test area for the study, and the land cover was classified into 6 different classes, such as the built-up area, forest, willow, grass, open land, and water. In the RF technique, the number of signatures were set as 5000, 10000, and 15000 and the related number of decision trees as 10, 50, and 100, respectively. As could be seen from the results of the study, the classification results of the combined multisource data sets had higher overall accuracies, and the result of 11 bands with the number of signatures set to 15000 and the decision trees set to 100, had the highest overall accuracy (92.68%). Машин сургалтын анамсаргүй ойн аргаар газрын бүрхэвчийг ангилахад харгалзан үзэх онцлогуудОрчин үеийн дүрсийн тоон боловсруулалтын зарим системд, машин сургалтын болон өндөр түвшингийн янз бүрийн аргууд бий болж байгаа бөгөөд судлаач өөрийн мэдлэг дээр тулгуурлан тухайн алгоритм дахь параметруудын утгуудыг зөв, оновчтой тодорхойлж өгснөөр өндөр чанарын үзүүлэлт бүхий сэдэвчилсэн үр дүнг гарган авах боломжтой. Энэхүү судалгаа нь SNAP Toolbox систем дээр машин сургалтын санамсаргүй ойн ангиллын алгоритмыг ашиглан газрын бүрхэвчийн ангилал хийхэд, ангиллын параметруудыг хэрхэн тохируулахыг харуулах үндсэн зорилготой бөгөөд нарийвчлалыг сайжруулах үүднээс олон эх сурвалжийн мэдээний сувгуудын 3 өөр янзын хоршлолыг ашиглав. Судалгааны загвар талбай болгон нийслэл Улаанбаатар хотын өмнөд хэсгийг сонгон авч, газрын бүрхэвчийг барилгажсан талбай, ой, бургас, өвс ургамал, сул газар, ус гэсэн үндсэн 6 ангид хуваан ангилсан бөгөөд сигнатурын тоог 5000, 10000, 15000, тэдгээрт харгалзах шийдвэрийн модыг 10, 50, 100 гэж тус тус тодорхойлов. Судалгааны үр дүнгээс харахад, оптикийн ба радарын нийлмэл мэдээг ангилсан үр дүнгүүд илүү өндөр ерөнхий нарийвчлалтай байсан бөгөөд сигнатурын тоог 15000, шийдвэрийн модыг 100 гэж тодорхойлсон 11 сувгийн үр дүн хамгийн өндөр нарийвчлалтай (92.68%) байсан болно.Түлхүүр үгс: Газрын бүрхэвч, SNAP, Машин сургалт, RF